2008
DOI: 10.1121/1.2936051
|View full text |Cite
|
Sign up to set email alerts
|

Rapid distinction of dumpsite objects using Multiple-Aspect Scattering - Results from scaled tank experiments

Abstract: Toxic dumpsites on the seafloor are causing increasing environmental concern, but traditional sonar imaging strains to distinguish objects in unconsolidated sediments, in particular in cluttered terrains. Scaled tank experiments were conducted with four different cylinders (fluid-filled and solid aluminium, air-filled and solid stainless steel, respectively) and two seabed types (silt and gravel), using the facilities at the University of Bath. The setup was a 10:1 scaled version of the EC-SITAR sea trials sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This aligns with Blondel's multistatic classification results, 13 which showed that different bistatic angles provided different information on target characteristics over the three aspect angles he examined.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…This aligns with Blondel's multistatic classification results, 13 which showed that different bistatic angles provided different information on target characteristics over the three aspect angles he examined.…”
Section: Resultssupporting
confidence: 51%
“…Simulation studies have been conducted in the multistatic space for spherical and cylindrical targets by Schmidt, Zampolli, and others to explore the implications of multiple mobile sources and receivers in a sonar network. [9][10][11] Tank and pond experiments by Dobbins, Blondel, Waters, and others [12][13][14][15][16] looked at different aspect angles on targets in a partial investigation of the multistatic scattering space. Ji et al describe simulation and tank experiments that include data collection on cylinders to examine impact of aspect and bistatic angle on scattering over a limited range of bistatic angles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation